Pengaruh Prediksi Kebangkrutan dan Kinerja Keuangan Perusahaan terhadap Harga Saham - Kusumawardani, Nistri (Media Akuntansi Perpajakan, 2025)
This study aims to analyze the effect of bankruptcy predictions and financial performance on stock prices of infrastructure companies listed on the Indonesia Stock Exchange for the 2022-2024 period. The study sample consisted of 69 companies selected using a purposive sampling method with a total of 54 observations. The data used were the companies' annual financial reports, analyzed using multiple linear regression using E-Views 12 software. The results showed that bankruptcy predictions had a negative but insignificant effect on stock prices, while financial performance had a positive and significant effect. These findings suggest that investors prioritize financial performance as a positive signal over bankruptcy risk when assessing company value.